Combined Air Oxidation and Activated Sludge Process for the Treatment of Refinery Spent Caustics - Yang, Qingsong; Kuang, Qianwen; Zhou, Yanbo; Lu*, Jun (Asian Journal of Chemistry, 2014)
Liquid hydrocarbon spent caustics generated in the oil refining process of a refinery contained a high concentration of toxic materials and refractory organic wastewater. In this study, the spent caustics were detoxified with a combination of air oxidation and biological treatment processes, as opposed to the direct biological treatment method. Further, the combined processes enabled the conversion of sulfate up to 95.5 % when the total sulfur load was 1.5 kgS/ (m3 d). The study indicated that the detoxification of sulfides to thiosulfates in the oxidation process enabled successful biological treatment and the combined air oxidation and biological treatment processes can effectively improve the oxidation rate of conversion, thereby reducing elemental sulfur generation rate. Furthermore, the combined processes can effectively shorten reaction time, thus increasing reaction load.